Kesiapsiagaan Masyarakat Daerah Tertinggal, Terdepan dan Terluar dalam Menghadapi Bencana Alam di Kabupaten Pulau Morotai - Irfan Hi Abd. Rahman; Amrin Sibua (Jurnal Ilmiah Wahana Pendidikan, 2020)
Earthquake disaster that has happened in morotai since 16 september 2017 had potentially 5.8 SR broke down public facilities, society's building and it impacted on psycology traumatic. the amount of loss arising from the disaster it is necessary to study steps so that the community is able to overcome the incident. Therefore, this research aimed to know the society in boarder area's preparadness in handling natural disaster. Th research methode used descriptive analysis with qualitative research where the ability of preparadness can be seen from the society's element such as shool,household and government. The result showed that the society"s understanding in preparadness and action related to disaster was still very minim, while respon emergency plan and aleret warning system jad the same portion and the same independent variable.